A relação entre espiritualidade e a formação do administrador na contemporaneidade - Cordeiro, Fábio Medeiros (2009)
Among many contemporary phenomena studied in the Sciences of Religion, the idea of spirituality can play an important and particular role in the field of business education. Our present study deals with the relation between Spirituality and Education of the businessman through certain bibliographic revision, placing it from the Science of Business Administration to the perspectives of work in the new scenario already known for the capitalist production and its configurations. Science of Business Administration is revisited and understood it in the process of rationalization of work and the new scenario of Post-Modernity. The multiple faces of Post- Modernity are here described considering them also as an object of our study. It indicates that spirituality is being studied in this complexity and that its relation has been built with intentionality. Spirituality as a significant component develops the education of the professional of the Business Administration.